Social Responsibility of PT Asam Jawa to the Impacted Community as a Social Conflict Management Strategy - Rahma Hayati Harahap; Afrizal *; Azwar * (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2019)
One important issue in the expansion of oil palm plantations in Indonesia is the massive escalative conflict between plantation companies and affected communities. This article discusses the conflict management by an oil palm plantation company, PT Asam Jawa. Using Lewis Coser's safety valve theory, this article presents the analysis of research about the impacts of the CSR program implemented by PT Asam Jawa on the dynamics of conflict between affected people and the company. The question answered is whether the application of CSR can be an alternative effort to manage conflicts between PT Asam Java and people affected, happening since the company started its operations. The results showed that although PT Asam Jawa implemented an extensive CSR program, the CSR program carried out by PT Asam Jawa did not function as a safety valve, because the people who were in conflict with companies related to the land used by PT Asam Jawa were excluded by the company as recipients of CSR funds.